PERWALIAN NASAB DAN HAK WARIS ANAK PEREMPUAN HASIL ZINA PERSPEKTIF HUKUM ISLAM - Iklil Hasbiyalla; Miftahul Arifin; Nur Mu'minah; Muhammad Abrori (SAMAWA, 2025)
The purpose of this study is to determine the concept of guardianship, nasaband inheritance rights of adulterated girls according to Islamic law. InIslam, guardianship of adulterated daughters can be granted to theirbiological father with the condition of recognition from the father. Unlikethe case with the nasab of adulterated girls in Islam, someone who givesbirth outside a valid marriage in shara', the nasab of children born fromthat marriage is fully related only to the mother. Similarly, the inheritancerights of adulterated daughters are when they are not related to their father,they will not receive inheritance from their father. Therefore, we areinterested in discussing the guardianship of nasab and the inheritance rightsof adulterated daughters from the perspective of Islamic law.